Newt regeneration genes regulate Wingless signaling to restore patterning in Drosophila eye. - Mehta, A.S.; Deshpande, P.; Chimata, A.V.; Tsonis, P.A.; Singh, A. (iScience, 2021)
Newts utilize their unique genes to restore missing parts by strategic regulation of conserved signaling pathways. Lack of genetic tools poses challenges to determine the function of such genes. Therefore, we used the Drosophila eye model to demonstrate the potential of 5 unique newt (Notophthalmus viridescens) gene(s), viropana1-viropana5 (vna1-vna5), which were ectopically expressed in L 2 mutant and GMR-hid, GMR-GAL4 eye. L 2 exhibits the loss of ventral half of early eye and head involution defective (hid) triggers cell-death during later eye development. Surprisingly, newt genes significantly restore missing photoreceptor cells both in L 2 and GMR>hid background by upregulating cell-proliferation and blocking cell-death, regulating evolutionarily conserved Wingless (Wg)/Wnt signaling pathway and exhibit non-cell-autonomous rescues. Further, Wg/Wnt signaling acts downstream of newt genes. Our data highlights that unique newt proteins can regulate conserved pathways to trigger a robust restoration of missing photoreceptor cells in Drosophila eye model with weak restoration capability.